Assessment of record keeping management in a Nigerian general hospital - Akor, Solomon Obotu; Omehia, Anthonia E.; Oladokun, Bolaji David (Record and Library Journal, 2024)
Background of the study: In the context of healthcare, record keeping management specifically involves the management of patient health records, administrative documents, and other pertinent information related to healthcare delivery Purpose: This study examines the record keeping management at General Hospital, Ikot Abasi, Akwa State of Nigeria. Four (4) specific objectives guided the conduct of the study. Methods: The survey descriptive design with a qualitative approach was used. Interview was used as the method of data collection. The study included a total of 11 participants, consisting of 2 medical doctors, 5 nurses, and 4 record administrators from the General Hospital, Ikot Abasi. Thematic analysis was employed to analyze the data collected from the interviews.  Findings: The study revealed a varying level of understanding among respondents regarding current record-keeping practices, with concerns raised about the accuracy and completeness of documentation. However, the study identified various challenges faced by healthcare professionals and administrators, including inconsistency in documentation practices, inadequate storage facilities, limited access to technology and resources, and compliance issues. Conclusion: The study concluded that the assessment of existing record keeping infrastructure and technology showed a positive impact, particularly with the implementation of EHR systems leading to streamlined processes and reduced reliance on paper-based documentation. The study recommends that health and other related organisations should implement standardized documentation protocols and provide regular training sessions for healthcare professionals to ensure consistency, accuracy, and completeness in record keeping.